The influence of locus of control, coping strategies and time perspective on post-traumatic growth in survivors with primary breast cancer - Alexandra-Cristina Paunescu; Marina Kvaskoff; Cyrille Delpierre; Lidia Delrieu; Guillemette Jacob; Myriam Pannard; Marie Préau (BMC Psychology)
Abstract Background Breast cancer, a potential traumatic stressor, may be accompanied by positive changes, such as post-traumatic growth (PTG), which may allow patients to overcome this stressful event more easily. Our aim was to identify factors associated with PTG in breast cancer survivors (BCSs). Methods We conducted a cross-sectional study in Seintinelles volunteers who answered online questionnaires. PTG was measured using the Post-Traumatic Growth Inventory (PTGI). Data on sociodemographic, health-related factors and lifestyle habits, fear of cancer recurrence, health locus of control, coping strategies, and time perspective were collected. Results The study included 821 BCSs aged 26 to 79 years, one to 16 years after cancer diagnosis. Mean of PTG scores were: relating to others 20.27 ± 6.61; new possibilities 14.00 ± 5.44; personal strength 12.24 ± 4.32; spiritual change 2.95 ± 2.54; appreciation of life 10.59 ± 3.00 and total PTG 60.05 ± 18.11. Several factors were associated with PTG: health-related factors (satisfaction with one’s own health, longer time since diagnosis), lifestyle habits (increasing physical activity level and stopping or reducing alcohol consumption after diagnosis), elements of locus of control (powerful others), coping strategies (positive thinking, seeking social support) and time perspective (present hedonistic), which were significantly positively associated with PTG. Chance locus of control and coping avoidance were inversely related to several PTG domains, even several years after diagnosis. Conclusions PTG may be increased in BCSs by acting on its modifiable factors. This includes adopting healthy behaviours, such as increasing physical activity and stopping/reducing alcohol consumption, and developing locus of control elements, such as powerful others, and coping strategies, such as positive thinking and seeking social support, through targeted interventions. Further studies, especially longitudinal studies, are needed to confirm the observed associations between health behaviours, health locus of control, time perspective, and PTG scores. Other measures, such as post-traumatic stress, should be considered because of possible inferences with PTG.